2016
DOI: 10.1002/acn3.372
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic SCN10A mutations in neuromuscular disease and epileptic encephalopathy

Abstract: ObjectivesTwo consanguineous families, one of Sudanese ethnicity presenting progressive neuromuscular disease, severe cognitive impairment, muscle weakness, upper motor neuron lesion, anhydrosis, facial dysmorphism, and recurrent seizures and the other of Egyptian ethnicity presenting with neonatal hypotonia, bradycardia, and recurrent seizures, were evaluated for the causative gene mutation.Methods and ResultsHomozygosity mapping and whole exome sequencing (WES) identified damaging homozygous variants in SCN1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…Features of Dravet syndrome have not been seen in our cohort, and no abnormal pain sensation have been reported for patients with Dravet syndrome and a (potentially) pathogenic SCN9A variant 43. For SCN10A variants, eight (potentially) pathogenic variants have been report as disease-causing in BrS, AF, SIDS, LGS, FIRES and autism 37–40. Multigenerational segregation with the disease in SFN families and/or functional testing in DRG neurons by cell electrophysiology indicate that the majority of the variants are causative for SFN (table 2).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Features of Dravet syndrome have not been seen in our cohort, and no abnormal pain sensation have been reported for patients with Dravet syndrome and a (potentially) pathogenic SCN9A variant 43. For SCN10A variants, eight (potentially) pathogenic variants have been report as disease-causing in BrS, AF, SIDS, LGS, FIRES and autism 37–40. Multigenerational segregation with the disease in SFN families and/or functional testing in DRG neurons by cell electrophysiology indicate that the majority of the variants are causative for SFN (table 2).…”
Section: Discussionmentioning
confidence: 57%
“…Eight (potentially) pathogenic SCN10A variants detected in our cohort of patients with pure SFN have been reported in patients with Brugada syndrome (BrS), atrial fibrillation (AF), sudden infant death syndrome (SIDS), Lennox-Gastaut syndrome (LGS), febrile infection-related epilepsy syndrome (FIRES) and autism 37–40. Only the patients with SFN with variant c.41G>T had arrhythmia.…”
Section: Resultsmentioning
confidence: 87%
“…In fact, the channel can be found in the CNS [70], offering the possibility of a broader involvement in neurological diseases. Additionally, recent research from Kambouris et al revealed mutations in SCN10A that can be linked to epilepsy [10].…”
Section: Discussionmentioning
confidence: 99%
“…Excitation/inhibition imbalance is a very popular hypothesis in the pathogenesis of autism [9]. It is known that voltage-gated sodium channels (VGSCs) play important roles in excitability of neurons and the mutations of VGSC genes result in a wide range of peripheral and central nervous system disorders [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Epilepsy is firmly linked to human variants in SCN1A, SCN2A, SCN3A, SCN8A, and SCN1B . Several other subunits, traditionally considered to be expressed at low levels in whole brain assays, have very restricted regional expression, for example, the “cardiac” sodium channel SCN5A within the limbic system and may ultimately prove to play contributory roles (SCN4A,, SCN5A, SCN7A, SCN9A, SCN10A). Although each channel participates in generating an action potential, the alpha subunits populate different neuronal subcompartments, play distinct kinetic roles in membrane electrogenesis, and offer multiple targets for subunit‐specific drugs.…”
Section: Nonuniform Channel Subunit Anatomy: From Single Neuron Compamentioning
confidence: 99%